Tempo máximo de fonação e características vocais acústicas de crianças pré-escolares - Capellari, Viviane Michele (2006)
The evaluation is the first step for any treatments. Therefore, normal parameters are the bases for proper evaluation in any kind of treatments. This study aimed at verifying measures of maximum phonation time (MPT) and vocal acoustic characteristics of 23 children aged 4 to 6.08 years, whose parents had signed a Free Consent Form. The children studied in four schools that agreed to participate in this research by signing an Institutional Authorization Form. The sampling process comprised a questionnaire that was sent to parents, auditory screening and vocal perceptive-auditory assessment, based on an independent evaluation performed by four speech and language pathologists through the use of R.A.S.A.T. scale. Data collection included MPT and voice samples for acoustic analysis through Multidimensional Voice Program (Kay Elemetrics). The results showed that MPT was significantly longer in 6-year-olds than in 4-year-olds; frequency variation was significantly higher in the total sample than at ages five and six. Noise harmonic ratio of the total sample was significantly higher than in fiveyear- olds. As age increased, values of noise harmonic ratio decreased significantly; noise harmonic ratio in 4-year-olds was significantly higher than at ages five and six. As the total mean of amplitude perturbation quotient increased, frequency variation, variation of amplitude and noise harmonic ratio also increased significantly; the same occurred between total mean of noise harmonic ratio and frequency variation. As the total means of amplitude perturbation quotient, frequency perturbation quotient and voice turbulence index increased the mean of soft phonation index decreased significantly. It was concluded that the results of the acoustic parameters and MPT at the age of four years old seem to evidenceimmaturity of the structures and lack of neural-muscular control at that age.